Amenability of gold ores to coarse particle gangue rejection (Preconcentration) processes - McGrath, Teresa; Wardell-Johnson, G.; Bax, A.; Eksteen, Jacques (2016)
© 2016 TAPPI Press. All rights reserved. Decreasing gold-in-ore grades is one of the main drivers of poorer productivity and rapidly escalating unit costs. Grinding costs, water use and reagent consumption are all intimately related to the ore grade processed. Various pre-concentration technologies have been developed that can be applied at various stages of crushing prior to ore grinding. This paper will review the amenability of ores to coarse particle barren gangue rejection for fine crush sizes in the pumpable particle size range (i.e., particles between 5 mm and 0.3 mm in size). The liberation of oxide gangue achieved during crushing is evaluated by proxy using sink-float analysis and the deportments of gold, sulfur, and arsenic into sinks and floats are monitored. Amenability of gangue rejection by continuous gravity separation is evaluated after various crushing modes (vertical shaft impact crushing, cone crushing, and HPGR crushing). The potential to identify coarse particle mineral association and liberation using three-dimensional x-ray computed tomography will be discussed.